Questionnaire Based Survey on Medicolegal Autopsy among Medical Students in Sikkim - Karma Mingur Diki Bhutia; Sankha Subhra Debbarma (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Contemplating the curriculum of an Indian Medical Undergraduate, demonstration of autopsyis still considered to be the cornerstone in Forensic Medicine. Medicolegal autopsy has always been perceivednegatively by the public either due to their religious beliefs or due to their preconceived notions or fear. Consideringthese prejudices, a study was undertaken not only to assess the knowledge, attitude & perception of a medicalundergraduate but also to understand the reflection of these societal stigma on a medical student.Material and Methods: A cross sectional survey was done on 200 medical students pursuing medicine in SMIMS,Gangtok, Sikkim who participated voluntarily in the study wherein structured questionnaire in google form wasdistributed through google link validated through their mail i.d. & registration number.Results: Out of 191 medical students, the number of students were predominantly females with the ratio of 1:1.30(M: F). 87.96% of the students knew that the medicolegal autopsy is done in all sudden, suspicious & unexpecteddeath. 90.05% strongly affirmed that the medicolegal autopsy ascertains the cause of death. The spectrum of easewith which the students watched the autopsy was almost along the same wavelength, 27.75% students werecomfortable, 25.13% were uncomfortable, 17.80% were indifferent while 29.32% were not yet exposed (due toonline teaching). Majority of students (93.72%) are interested in watching watch more of postmortem examination.Conclusions: The attitude of the students were optimistic towards autopsy & awareness among the participantswas found to be acceptable. However, there were still a lot of grey areas that needed to be addressed.